2019
DOI: 10.3390/jcm8101641
|View full text |Cite
|
Sign up to set email alerts
|

More Impaired Dynamic Ventilatory Muscle Oxygenation in Congestive Heart Failure than in Chronic Obstructive Pulmonary Disease

Abstract: Patients with chronic obstructive pulmonary disease (COPD) and congestive heart failure (CHF) often have dyspnea. Despite differences in primary organ derangement and similarities in secondary skeletal muscle changes, both patient groups have prominent functional impairment. With similar daily exercise performance in patients with CHF and COPD, we hypothesized that patients with CHF would have worse ventilatory muscle oxygenation than patients with COPD. This study aimed to compare differences in tissue oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…In terms of placement of the NIRS optodes, 23 studies monitored NIRS parameters of the vastus lateralis (VL) and one study monitored the vastus medialis (VM). 31 Six studies evaluated the 7th intercostal muscle (IC), 17 , 21 , 37 , 39 , 49 , 50 one study monitored the serratus anterior (SA), 35 and one study examined the abdominal muscles, over the upper rectus abdominis. 21 Eight studies evaluated oxygenation of the cerebral cortex 9 , 13 , 36 , 41 43 , 47 , 50 and two studies examined the VL in conjunction with the cerebral cortex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of placement of the NIRS optodes, 23 studies monitored NIRS parameters of the vastus lateralis (VL) and one study monitored the vastus medialis (VM). 31 Six studies evaluated the 7th intercostal muscle (IC), 17 , 21 , 37 , 39 , 49 , 50 one study monitored the serratus anterior (SA), 35 and one study examined the abdominal muscles, over the upper rectus abdominis. 21 Eight studies evaluated oxygenation of the cerebral cortex 9 , 13 , 36 , 41 43 , 47 , 50 and two studies examined the VL in conjunction with the cerebral cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies that reported changes in oxygen extraction (HHb) of VL (n = 8), all reported a statistically significant increase in this value in response to cycling in COPD ( Table 2 ). Of the studies that monitored VL or VM StO2 (n = 11), most studies 2 , 20 , 31 , 35 , 36 , 38 , 39 , 45 , 48 reported a decrease in this value, whereas two studies reported unchanging levels of VL StO 2 ( Table 2 ). 5 , 37 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Habedank and colleagues showed that PI max , generally measured as a respiratory muscle function, was not an independent predictor of prognosis because it varied according to gender, BMI, and cachexia in patients with severe HFrEF [11]. A recent study has shown impaired respiratory muscle oxygenation during exercise in patients with HF, leading to breathlessness and decreased quality of life [23]. In the present study, the higher change in PI max was associated with lower respiratory muscle strength at the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-test preparation was followed the standard guide and bronchodilators were not administered within 3 h for short-acting beta-agonists and 12 h for long-acting betaagonists before the tests. [27][28][29] FEV 1 , FVC, TLC, RV, and D L CO were measured using spirometry, body plethysmography, and the single-breath technique (MasterScreenTM Body; Carefusion, Wuerzburg, Germany), respectively, in accordance with the currently recommended standards by submit your manuscript | www.dovepress.com…”
Section: Pulmonary Function Testingmentioning
confidence: 99%